2011
DOI: 10.1002/pssc.201000762
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, dielectric and structural properties of borovanadate glass systems doped with samarium oxide

Abstract: Glasses doped with rare earth (RE) ions are widely studied due to the numerous applications of these systems (active media for solid state lasers, optical telecommunication, non‐linear optical materials, electro‐optic devices, etc.). Boron trioxide, B2O3, is a known glass forming oxide with a relative low melting temperature. The addition of a transition metal oxide, such as V2O5, promotes the exhibition of semiconducting properties making these promising systems for several technological applications, such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…It can be observed that conductivity was very minimal for temperature upto 400K and started increasing then onwards. The conductivity of the present glasses is more than reported values for Sm2O3-B2O3-V2O5 -Li2O glasses [8] and Sm2O3- B2O3-Al2O3 -Na2O-CuCl2 glasses [9] by a few orders of magnitude. However, it is less than that reported for V2O5-SeO2-ZnO glasses [2] and V2O5-ZnO and glasses [4].…”
Section: Electrical Conductivitycontrasting
confidence: 52%
See 1 more Smart Citation
“…It can be observed that conductivity was very minimal for temperature upto 400K and started increasing then onwards. The conductivity of the present glasses is more than reported values for Sm2O3-B2O3-V2O5 -Li2O glasses [8] and Sm2O3- B2O3-Al2O3 -Na2O-CuCl2 glasses [9] by a few orders of magnitude. However, it is less than that reported for V2O5-SeO2-ZnO glasses [2] and V2O5-ZnO and glasses [4].…”
Section: Electrical Conductivitycontrasting
confidence: 52%
“…It also acts as a modifier and as well as network former [6,7]. Samarium oxide (Sm2O3) is a rare earth oxide used for enhancing physical, electrical, dielectric and optical properties of glasses [8,9]. A limited literature exists on Sm2O3 and TMI doped borate glasses.…”
Section: Introductionmentioning
confidence: 99%